DETERMINANT OF THE CUSTOMER INTEREST FACTOR IN USING BSI MOBILE BANKING - Dila Reski Wulandari; Kurniawati Meylianingrum (I-Finance Journal, 2024)
This study aims to describe and describe the percentage level of perceived ease of use, perceived effectiveness, feature availability, and security in the interest in using mobile banking. The population in this study is customers who use the Bank Syariah Indonesia Mobile Banking application in Malang City.  As for the calculation of the slovin formula, it was found that the number of samples used in this study amounted to 385 people. Sampling in this study uses nonprobability sampling with purposive sampling technique. The data analysis technique used is using multiple regression with hypothesis tests, namely t test and F test through SPSS 25 software. The results of the study showed that based on the results of the t-Test test, the perceived ease of use variable had a significant positive effect on the interest in using, the perceived effectiveness variable had no effect, the feature availability variable had a negative effect, the security variable had a significant positive effect on the interest in using the BSI mobile banking application, and the results of the F-Test showed that simultaneously, the independent variable (perceived ease of use, perceived effectiveness,  feature availability, and security) have a significant effect on interest in using BSI mobile banking. With the conclusion that perceived ease of use significantly increases customer interest in using BSI mobile banking in Malang City, while perceived effectiveness, feature availability, and security do not have a significant influence partially, but simultaneously these four variables significantly increase customer interest.